Taxes and pay without performance: Evidence from executives - Laura Arnemann (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
This paper contributes to the ongoing discourse on the taxation of top-income earners by empirically investigating the impact of tax policy changes on pay without performance. Using data on executive compensation in the United States, I compare the sensitivity of executive compensation to performance shocks beyond the executives control before and after a change in the federal and state tax rate. Performance shocks beyond the executives control are measured using exogenous export demand shocks. I find that the effect of taxes on pay without performance depends on the type of tax levied. Specifically, state tax hikes increase the sensitivity of executive compensation to performance shocks exogenous to executive effort. Conversely, changes in federal tax rates have a negative but statistically insignificant effect on pay without performance. Pay without performance changes most in response to state tax hikes for executives with greater mobility. Based on a Nash bargaining model, I outline that these heterogeneous findings can be explained by the importance of outside options for the pass-through of exogenous profit shocks to executive earnings. Firms need to increase compensation more in response to exogenous performance shocks after a state tax hike to retain the executive.
Keywords: H22; H24; M12; 330; Tax Incidence; Rent-Sharing; Executive Compensation